Exhibition attachment: effects on customer satisfaction, complaints and loyalty. Issue 6 (2nd June 2020) - Zhan, Fenping; Luo, Wenwei; Luo, Jiayi
ABSTRACT: This study examines the relationship among dimensions of exhibition attachment, customer satisfaction, complaints and loyalty by constructing the structural model on the theories of place attachment and American Customer Satisfaction Index. The model tested on attendees participating the Chinese Beauty Exposition showed that (1) Dimensions of exhibition attachment significantly and positively influences customer satisfaction and loyalty; (2) Dimensions of exhibition attachment indirectly positively affect customer loyalty and negatively influence complaints through satisfaction; (3) Affective attachment has stronger negative impact on customers complaints than functional dependence does. Based on these findings, both theoretical and practical implications are discussed.